Public-Private Partnership in Telecommunications Infrastructure Projects : Case of the Democratic Republic of Congo - World Bank (Washington, DC, 2013)
This paper outlines the role of government in infrastructure Public-Private Partnerships (PPP) in the telecommunication industry in the Democratic Republic of Congo. It also summarizes the state of Congo's telecommunication infrastructure, the advantages of Open Access Network (OAN) as a Broadband PPP Business Model, as well as risks allocated to the implementation of the project and proposes the World Bank Group risk mitigation instruments.